Why Bernie Sanders Should Support Utilizing Expanded Vaccine Production to Advance Democratic Socialism at Home and Abroad (AmeriQuests, 2022)
The Bernie Sanders platform needs to expand its foreign policy and health care plans to include continued investment in the development of vaccines for other viruses following the COVID-19 pandemic to advance the principles of democratic socialism at home and internationally.